Does the quality of preoperative closed reduction of displaced ankle fractures affect wound complications after surgical fixation?. Issue 10 (October 2018) - Chien, Bonnie Y.; Stupay, Kristen L.; Miller, Christopher P.; Smith, Jeremy T.; Briceno, Jorge; Kwon, John Y.
Abstract: Background: Displaced ankle fractures are initially closed reduced and splinted with the goal of restoring gross ankle alignment. The benefits of an exact closed reduction are unclear and possibly detrimental and unnecessary if multiple attempts are made. The purpose of this study was to determine whether the quality of preoperative closed reduction in patients with operative ankle fractures affects post-operative wound complications. Methods: A retrospective analysis was performed of patients with isolated, closed, operative ankle fractures treated at two level 1 trauma centers who had an initial closed reduction performed on presentation. Patient demographics, fracture characteristics, data pertinent to the reduction, and post-operative wound complications were collected. A novel grading system to assess reduction quality was developed, applied, and evaluated for inter- and intra-observer agreement. Results: 161 patients met inclusion criteria for analysis. 17% (27/161) sustained a post-operative wound complication. There was no statistically significant association between wound complications and quality of preoperative closed reduction (p = 0.17) nor with multiple reduction attempts (p = 0.887). However, patients with poor initial reductions had a decreased mean time to surgery (1.4 ± 2.9 versus 4.7 ± 6.3 days, p = 0.03), which may have been protective. Interclass correlation coefficients for inter- and intra-rater reliability of the classification schema was 0.942 and 0.922, respectively, demonstrating excellent agreement. Conclusion: There was no association between preoperative closed reduction quality and incidence of post-surgical wound complications in patients with operative ankle fractures when analyzing the variables assessed in this investigation. While initial ankle reduction is still recommended, multiple attempts to achieve a perfect reduction are likely unnecessary.